2008
DOI: 10.1037/0735-7028.39.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Sexual issues and aging within the context of work with older adult patients.

Abstract: Recent studies suggest that the majority of older men and women maintain moderate or high levels of sexual interest well into their 70s but often experience sexual dysfunction. Given the burgeoning of the older adult population, psychologists are increasingly likely to find older patients in their practice with questions or concerns about sexuality. The goal of this article is to provide psychologists with current information regarding sexuality and aging, including general prevalence data, age-related biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…Asking permission to talk about sex with an older adult conveys sensitivity and respect, while placing the control in the hands of the client (Hillman, 2008). When exploring topics related to sexual activity, it is important to avoid conveyance of subtle assumptions (Crisp & McCave, 2007) that older adults do not, or should not, have sex; therefore asking "how often" rather than "do you" can make a significant difference in the therapeutic alliance.…”
Section: Trainingmentioning
confidence: 99%
“…Asking permission to talk about sex with an older adult conveys sensitivity and respect, while placing the control in the hands of the client (Hillman, 2008). When exploring topics related to sexual activity, it is important to avoid conveyance of subtle assumptions (Crisp & McCave, 2007) that older adults do not, or should not, have sex; therefore asking "how often" rather than "do you" can make a significant difference in the therapeutic alliance.…”
Section: Trainingmentioning
confidence: 99%
“…The experience of sexuality and aging is as diverse as the population of older adults (Hillman, 2008). The National Social Life, Health, and Aging Project (NSHAP) enrolled over 3,000 men and women, aged 57 to 85 and found that the quality of, and interest in, sex was associated with good health (Githens & Abramsohn, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant number of other medications commonly used among older adults also affect sexual functioning and are known to be associated with ED. These include many anti-depressants, anti-anxiety, anti-hypertensive, and even over-the-counter anti-histamines (Hillman 2008; see http://www.webmd.com/ erectile-dysfunction/guide/drugs-linked-erectile-dysfunction for a comprehensive and updated listing). Asboe et al (2007) reported that increasing age was strongly associated with ED and low sexual desire among older HIV-positive men.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…For instance, Loe (2004) reports that for some women, when partners use ED medications, there may be both relief that sexual activity can continue and fear of side effects, and unwanted sex. Almost no research exists that addresses other issues of sexual dysfunction among older women living with HIV (Hillman 2008). Given the mandate that older adults living with HIV have a right to fully enjoy their sexuality, it will be important to develop a better understanding of the issues related to sexual dysfunction for older adults living with HIV.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%